Modified DOP-PCR for improved STR typing of degraded DNA from human skeletal remains and bloodstains. (January 2016) - Ambers, Angie; Turnbough, Meredith; Benjamin, Robert; Gill-King, Harrell; King, Jonathan; Sajantila, Antti; Budowle, Bruce
Highlights: Forensic and ancient DNA samples often are damaged and in limited quantity. Several strategies exist to address challenges of degraded and low copy DNA. We used a WGA method called degenerate-oligonucleotide-primed PCR (DOP-PCR). This study assessed the efficacy of four modified DOP-PCR primers. Each primer improved STR profiles from human skeletal remains and bloodstains. Abstract: Forensic and ancient DNA samples often are damaged and in limited quantity as a result of exposure to harsh environments and the passage of time. Several strategies have been proposed to address the challenges posed by degraded and low copy templates, including a PCR based whole genome amplification method called degenerate oligonucleotide-primed PCR (DOP-PCR). This study assessed the efficacy of four modified versions of the original DOP-PCR primer that retain at least a portion of the 5′ defined sequence and alter the number of bases on the 3′ end. The use of each of the four modified primers resulted in improved STR profiles from environmentally-damaged bloodstains, contemporary human skeletal remains, American Civil War era bone samples, and skeletal remains of WWII soldiers over those obtained by previously described DOP-PCR methods and routine STR typing. Additionally, the modified DOP-PCR procedure allows for a larger volume of DNA extract to be used, reducing the need to concentrate the sample and thus mitigating the effects of concurrent concentration of inhibitors.